2022
DOI: 10.3389/fnut.2022.901944
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of ultrasound-assisted extraction of naturally occurring glucosinolates from by-products of Camelina sativa L. and their effect on human colorectal cancer cell line

Abstract: The food waste generated by small and medium agro-industrial enterprises requires appropriate management and valorization in order to decrease environmental problems and recover high-value products, respectively. In this study, the Camelina sativa seed by-product was used as a source of glucosinolates. To begin, the chemical profile of the extract obtained using an international organization for standardization (ISO) procedure was determined by UPLC-HRMS/MS analysis. In addition, an extraction method based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 30 publications
2
11
1
Order By: Relevance
“…We determined the average total glucosinolate concentration to be 8.39 mg/g in camelina seeds (wet-basis results) and 15.95 mg/g in the defatted meal ( Table 3 ). In a recent study, Pagliari et al [ 28 ] reported 5.69 mg/g as the average total glucosinolate result in camelina-defatted meals using a rapid and green method, which is approximately 3-fold lower than our result. Matthäus and Zubr [ 38 ] reported the total content of glucosinolates to be in the range of 4.68–9.88 mg/g in camelina seeds and 7.54–12.17 mg/g in camelina defatted meal (oilseed cake).…”
Section: Resultscontrasting
confidence: 81%
See 2 more Smart Citations
“…We determined the average total glucosinolate concentration to be 8.39 mg/g in camelina seeds (wet-basis results) and 15.95 mg/g in the defatted meal ( Table 3 ). In a recent study, Pagliari et al [ 28 ] reported 5.69 mg/g as the average total glucosinolate result in camelina-defatted meals using a rapid and green method, which is approximately 3-fold lower than our result. Matthäus and Zubr [ 38 ] reported the total content of glucosinolates to be in the range of 4.68–9.88 mg/g in camelina seeds and 7.54–12.17 mg/g in camelina defatted meal (oilseed cake).…”
Section: Resultscontrasting
confidence: 81%
“…In addition, the desulfation rate can vary within the column and yield results that will overestimate or underestimate the total glucosinolate concentration [ 25 , 26 ]. With the increased sensitivity and specificity that the modern liquid chromatography instrument and column can provide, direct measurement of intact glucosinolates may be feasible, and the desulfation steps can be omitted when the method is carefully designed [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…GLSs composition and concentration vary based on species, variety, environment conditions, plant age. ( Fahey et al, 2023 , Mithen, n.d. , Ram Bhandari et al, 2015 , Pagliari et al, 2022a ). Recent studies have associated GLSs with several health benefits such as antioxidant (direct and indirect), anti-inflammatory, antimicrobial, cholinesterase inhibitory, anti-tumor, and cardiovascular disease preventive properties ( Maina et al, 2020 , Sánchez-Pujante et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Under the optimized extraction conditions, the developed PLE method was compared with conventional methods such as ISO and USAE ( Pagliari et al, 2022a ) showing better efficiency, with a reduction of time and solvent consumption. Finally, the biological activities of the GLSs identified in PC, which are still poorly known, were investigated using in silico and in vitro assays to identify their potential beneficial activity for human health.…”
Section: Introductionmentioning
confidence: 99%